Physicochemical and microbiological properties of Finger Millet and Defatted Sesame seeds flours used as complementary foods - Terhemba, Seember; Ariahu, Charles; Gbuusu, Bem; Terhemba, U. I; Nember, T. I; Ariahu, E. C (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2024)
Finger millet and defatted sesame seeds were studied subject to germination and / or natural fermentation. Various kinds of treatment were given to the product which gave rise to non-germinated (NG) and non-fermented (NF) finger millet, germinated non-fermented (GN) and germinated fermented (GF) finger millet plus defatted sesame flour. Cerelac - commercial maize + soybean product was used as control with samples were formulated to provide 16g protein/100g solid based on their proximate composition using material balancing. Moisture content of complementary food ranged from 7.66- 8.13g/100g. Carbohydrate ranged from 63.92- 64.93g/100g with an equal increase in energy value from 368.04- 369.61kJ/100g. Also, the mineral content of complementary foods showed similar increase for calcium: 252.80- 281.10mg/100g, potassium: 946.35- 994.13mg/100g, iron: 4.87- 6.61mg/100g, zinc: 10.21- 11.45mg/100g with germination and fermentation. As expected, anti-nutritional factors reduced to acceptable values with oxalate ranging from 0.26- 1.96g/100g, tannins 0.44- 1.92g/100g, phytate 0.37- 2.31g/100g and cyanides 0.34-2.13g/100g. Total viable counts (cfu/g) ranged from 0.2×103 - 1.6×103 while there was no detection of E.coli in the samples.